Construcción afectiva de la corporalidad: la vieja y su joven amante en Pluto de Aristófanes (vv. 959-1096) - Fernández, Claudia Nélida (2021)
After Plutus’s recovery of his eyesight and the subsequent redistribution of wealth, an old woman, probably a hetaira, is suddenly abandoned by her young lover, who is now financially solvent and in no more need of her (Aristophanes’ Plutus , ll. 959-1096). The expression of her complaints —in front of Chremylus, the comic hero, and also of the young man, who approaches the hero’s house in order to express his gratitude to the god— results in an episodic scene devoted to the exposition of material precariousness of her decayed body. Behind this comic denigration, usual against old and ugly persons, there are also exposed various forms of body apprehension very subtly, on which this paper intends to explore. We refer to the affective and sensitive construction of corporality, to the dynamics of body language, to the physiological imprint of immateriality (such as pleasure or pain), among several aspects that prove the author’s special interest in the body.